Compensation and Culture: A Configurational Fit between Pay System and Culture Types - Guzak, James R.; Crandall, Barbara; Alavinejad, Hoda (Journal of Organizational Psychology, 2017)
For most companies, compensation represents the largest single expenditure, and compensation is recognized as an important mechanism for organizational performance. Pay strategies also have the important role of underpinning and supporting organizational culture, and research suggests that failure to support organizational culture can precipitate a company’s failure. Understanding the convergence of these two domains represents an important area of research. We propose that four different culture classifications might each be supported by unique combinations of either an egalitarian or hierarchical pay distribution, in combination with or without pay-for-performance compensation strategies.